2022
DOI: 10.3390/jcm11040967
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Hexanic Extract of Serenoa repens vs. Watchful Waiting in Men with Moderate to Severe LUTS-BPH: Results of a Paired Matched Clinical Study

Abstract: We investigated changes in symptoms and quality of life (QoL) in men with moderate-to-severe lower urinary tract symptoms associated with benign prostatic hyperplasia (LUTS/BPH) receiving the hexanic extract of Serenoa repens (HESr) and compared results with a matched group on watchful waiting (WW). Data was from a real-world, open-label, prospective, multicenter study. This sub-group analysis included patients with moderate-to-severe symptoms receiving either the HESr 320 mg/daily for six months (HESr) or who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, a recent qualitative analysis showed that side effects affecting sexual function are of greater importance than non-sexual side effects for sexually active patients [32]. In that regard, HESr has been shown to improve symptoms and QoL in BPH patients, but with only limited side effects, which do not impact sexual function [1,7,10,11,33], and this could help to maintain adherence in patients worried about the effect of medical LUTS/BPH treatment on their sexual function. The HESr is recommended in the recent EAU Guidelines as a treatment "for men with LUTS who want to avoid any potential adverse events especially related to sexual function" [1].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent qualitative analysis showed that side effects affecting sexual function are of greater importance than non-sexual side effects for sexually active patients [32]. In that regard, HESr has been shown to improve symptoms and QoL in BPH patients, but with only limited side effects, which do not impact sexual function [1,7,10,11,33], and this could help to maintain adherence in patients worried about the effect of medical LUTS/BPH treatment on their sexual function. The HESr is recommended in the recent EAU Guidelines as a treatment "for men with LUTS who want to avoid any potential adverse events especially related to sexual function" [1].…”
Section: Discussionmentioning
confidence: 99%
“…For example, urinary incontinence, or involuntary leakage of urine, is one of the most commonly investigated sources of LUTS and reportedly affects between 13%-46% of Australian women 16 . However, urinary incontinence is an umbrella term which encompasses a range of leakage sub-types, such as stress urinary incontinence (SUI, leakage during physical activity), urge urinary incontinence (UUI, leakage associated with urgency) and mixed urinary incontinence [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses focusing only on HESr found that HESr treatment reduced nocturia and improved maximum urinary flow rate (Qmax) compared to placebo and had a similar favourable effect on LUTS as the α-blocker tamsulosin and short-term 5-ARIs [ 29 , 30 ]. In addition, a recent paired matched clinical study demonstrated greater improvements of symptoms and QoL in patients treated with HESr versus watchful waiting [ 31 ]. The body of published clinical evidence therefore needs to be interpreted with caution.…”
Section: Overview Of Hesr Monotherapy In the Management Of Luts/bphmentioning
confidence: 99%